Vital Tooth Whitening Techniques. A Literature Review - Kirk, Pia Chatterjee (Current Dentistry, 2021)
BackgroundVital tooth whitening has become an integral part of esthetic dentistry and remains one of the safest and most economical options today to improve dental esthetics without removing tooth structure. The tooth whitening materials have evolved into three categories: dentist-prescribed/dispensed in office, the dentist prescribed patient home use, and over-the-counter purchased and applied by patients.ObjectiveThis review outlines the latest advances in dentist prescribed vital teeth whitening techniques, effects on tooth structure, soft tissues, and dental restoratives. Areas requiring additional research are also discussed.MethodsAn electronic and manual literature search was conducted for keywords such as tooth bleaching and dental bleaching techniques using PubMed/MEDLINE, followed by a manual selection of the studies that included whitening procedures in vital teeth.ResultsThe two main whitening agents are carbamide peroxide (CP) and hydrogen peroxide (HP or H2O2) whose concentration, duration of contact and total treatment time can alter results. In addition, factors including the type of stain and the age of the patient can affect results. Although whitening agents can affect tooth structure, restorative materials, and gingival tissues, the changes are temporary or can be treated using minimally invasive techniques.ConclusionAreas requiring further research include the actual mechanism of whitening, its effect on tooth structure and restorative materials, and the development of an easy method to quantitate the degree of whitening in the dental office.
Keywords: tooth bleaching